Diagnóstico de necesidades y propuesta de un plan de capacitación para emprendedores, en la ciudad de Cañar de la provincia del Cañar, 2022 - Pinguil Guamán, Johanna Aurora (2024)
Entrepreneurial activity refers to the innovation of creating new companies, which is why entrepreneurs must be constantly acquiring knowledge, for the generation of wealth and social economic development. For this study, the entrepreneurs of the association were taken into account. Chagrana. The main objective of carrying out this research was to design a “Training Plan for entrepreneurs in the city of Cañar of the Cañar Province, based on a diagnosis of training needs to improve skills, knowledge and abilities”, in which its objectives specific are: “Identify what skills entrepreneurs in the city of Cañar need to develop.” And “Verify the level of theoretical and practical knowledge that entrepreneurs have.” It was based on investigating the training needs of the 37 entrepreneurs who are active, taking into account the total number of entrepreneurs in the association, which is entrepreneurs, and developing the activity plan to train the entrepreneurs who make up the Chagrana association with content that allows improve the conditions of both the entrepreneur and his ventures, those responsible, proposals, etc., for the execution of this plan a budget of $1070,25 is needed. Finally, conclusions and recommendations were presented, in this way the bibliographies and the corresponding annexes. It was concluded that the entrepreneurs have received training provided by outside entities or third parties and do not have the situational diagnosis of needs to be able to carry out the programming of the training, and thus meet the needs of implementing strategies that lead to an increase in the socio-economic well-being of the entrepreneurs. entrepreneurs from the Chagrana association. Therefore, it is proposed that this training plan be implemented to strengthen knowledge, skills, attitudes, in order to satisfy the requirements of entrepreneurs.